2015
DOI: 10.1186/s12861-015-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty gene dosage influences temporal-spatial dynamics of primary enamel knot formation

Abstract: Background: The mouse embryonic mandible comprises two types of tooth primordia in the cheek region: progressive tooth primordia of prospective functional teeth and rudimentary tooth primordia in premolar region -MS and R2. Mice lacking Sprouty genes develop supernumerary tooth in front of the lower M1 (first molar) primordium during embryogenesis. We focused on temporal-spatial dynamics of Sonic Hedgehog expression as a marker of early odontogenesis during supernumerary tooth development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…In the lower jaw, we observed a similar tendency, with R2 and M1 signaling centers occasionally coexisting only in DUHi, but never in FVB ( Supplementary Figures 6 and 7). In both strains, the lower R2 signaling center was ultimately part of the mature M1 signaling center known as the pEK (Supplementary Figure 2 R and P), as shown for other mouse strains (Lochovska et al, 2015).…”
Section: The Premolar Signaling Center Persists Longer In Duhi Than Isupporting
confidence: 53%
See 2 more Smart Citations
“…In the lower jaw, we observed a similar tendency, with R2 and M1 signaling centers occasionally coexisting only in DUHi, but never in FVB ( Supplementary Figures 6 and 7). In both strains, the lower R2 signaling center was ultimately part of the mature M1 signaling center known as the pEK (Supplementary Figure 2 R and P), as shown for other mouse strains (Lochovska et al, 2015).…”
Section: The Premolar Signaling Center Persists Longer In Duhi Than Isupporting
confidence: 53%
“…The primordium known as "R2" has been linked to the last premolar (Lesot et al, 1998;Peterkova et al, 1996;Peterková et al, 2002;Prochazka et al, 2010;Viriot et al, 2002). In the lower jaw, the R2 signaling center interacts in a complex manner with the signaling center of the first molar (Lochovska et al, 2015;Prochazka et al, 2010;Sadier et al, 2019). In CD1 mice, R2 and early M1 signaling center transiently co-exist before fusing to form the mature M1 signaling center known as the pEK (Lochovska et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that two successive and transient bud‐like structures in the diastema may be the rudimentary precursors of the premolars present in ancestral species (Prochazka et al, ). These rudimentary buds can develop into a supernumerary tooth in several mutants (Klein et al, ; Lochovska et al, ). It will be interesting to further investigate if the expanded tooth germ upon increased Shh activity can contribute to supernumerary tooth formation.…”
Section: Molar Progenitor Cell Migrationmentioning
confidence: 99%
“…chr5: 141405828 is located in the γ-protocadherin (PCDHG@) gene cluster, which is believed to modulate regulatory pathways critical for development, such as Wnt signalling [Dallosso et al, 2009], which is also critical at all stages of tooth development. rs66756037 is located near the genes fibroblast growth factor 1 (FGF1) and sprouty RTK signalling antagonist 4 (SPRY4), both of which are involved in tooth development [Thesleff et al, 2001;Lochovska et al, 2015]. In regions 2q37 and 10q21.1, there were clusters of 16 and 19 suggestively significant SNPs, respectively.…”
Section: Gwas On Malesmentioning
confidence: 99%